Betsy Mix Cowles : champion of equality - Robertson, Stacey M. (Lives of American women., 2014)
"Betsy Mix Cowles--a bold reformer whose circle of acquaintances included Frederick Douglass, Abby Kelley, and William Lloyd Garrison--is a brilliant example of what an educated and independent woman can accomplish. A staunch defender of abolitionism, Cowles also took up the cause of women's rights and dedicated her life to the advocacy of women's access to education, equal rights, and independence in the pre-Civil War era. The life of this devoted social reformer illuminates the struggles and historical developments relating to abolitionism and the fledgling women's movement during one of the most contentious periods in American history. About the Lives of American Women series: Selected and edited by renowned women's historian Carol Berkin, these brief biographies are designed for use in undergraduate courses. Rather than a comprehensive approach, each biography focuses instead on a particular aspect of a women's life that is emblematic of her time, or which made her a pivotal figure in the era. The emphasis is on a "good read," featuring accessible writing and compelling narratives, without sacrificing sound scholarship and academic integrity. Primary sources at the end of each biography reveal the subject's perspective in her own words. Study questions and an annotated bibliography support the student reader"--